A green scheduling algorithm for flexible job shop with energy-saving measures - Wu, Xiuli; Sun, Yangjun (Journal of cleaner production, 2018)
We study how to save energy from the viewpoint of operation management. When to turn-on/off machines and which speed level to choose are two measures we employ to save energy. We focus on the flexible job shop scheduling problem. To begin with, a model is formulated for the flexible job shop scheduling problem when the two energy-saving measures are under consideration. An energy consumption model is proposed to compute the energy consumption for a machine in different states. Then, a non-dominated sorted genetic algorithm is developed to solve the problem. In the non-dominated sorted genetic algorithm, a green scheduling heuristic is presented to optimize the makespan, the energy consumption and the numbers of turning-on/off machines simultaneously. Finally, the comprehensive experiment results prove that the proposed model and the algorithm can solve the problem effectively and efficiently.